PRZYGOTOWANIE DO PRACY Z UCZNIAMI O SPECJALNYCH POTRZEBACH EDUKACYJNYCH: JĘZYKOWE NARZĘDZIA DIAGNOSTYCZNE W PRAKTYCE NAUCZYCIELSKIEJ - Karpińska-Szaj, Katarzyna (Neofilolog, 2019)
Adapting foreign language teaching to the requirements of students with special educational needs requires prior diagnosis of the developmental potential of the pupils concerned. Because of the educational and rehabilitative character of foreign language learning in students with language and speech deficiencies, the diagnosis addresses the possibilities of using foreign language learning in developing general and linguistic competencies in both languages (native and foreign). The article presents the aims of diagnosing linguistic communicative competencies in the context of foreign language teaching. The differences between speech diagnosis and diagnosis performed for the needs of foreign language teaching are discussed, based on cases of pupils with deficiencies in their native language (Polish). The evaluation of the students’ competencies involved reformulation as an instrument of linguistic diagnosis; learning strategies were also considered in the assessment.